Pengembangan E-Modul Dengan Pendekatan SETS Materi Struktur Atom Kelas XI Di Madrasah Aliyah Rudhatut Thullab Siak Kecil - Putri Nabila; Arief Yandra Putra; Asmadia Asmadia; Nely Agustin (LPPM Universitas Negeri Jakarta, 2025)
This study aims to develop and determine the level of validity and practicality of chemistry e-modules with the SETS (Science, Environment, Technology and Society) approach on atomic structure material grade XI at Madrasah Aliyah Raudhatut Thullab Siak Small. This research uses the ADDIE development model which consists of the stages of analysis, design, development and implementation. Data collection techniques include validation of material and media experts and user response tests from teachers and students. Instruments in the form of validation questionnaires and user response questionnaires were analyzed using a Likert scale. This e-module was developed using Canva and through Flipbook Publu. Based on the results of the study, the e-module was declared very feasible with a score of 91.30% and feasible to use in learning chemistry at school.